2020
DOI: 10.1029/2019gc008819
|View full text |Cite
|
Sign up to set email alerts
|

Constraints on the Rheology of the Lithosphere From Flexure of the Pacific Plate at the Hawaiian Islands

Abstract: The rheology of oceanic lithosphere is important to our understanding of mantle dynamics and to the emergence and manifestations of plate tectonics. Data from experimental rock mechanics suggest rheology is dominated by three different deformation mechanisms including frictional sliding, low‐temperature plasticity, and high‐temperature creep, from shallow depths at relatively cold temperatures to large depths at relatively high temperatures. However, low‐temperature plasticity is poorly understood. This study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(29 citation statements)
references
References 51 publications
6
23
0
Order By: Relevance
“…The first is that the flexural rigidity of the lithosphere along the Hawaiian chain appears significantly weaker than predicted by the relevant, laboratory‐derived rheological laws and assuming a normal 90‐Myr geotherm (Bellas et al., 2020; Pleus et al., 2020; Zhong & Watts, 2013). Given that it is unlikely that solid‐state convection can induce such a shallow temperature anomaly, it was argued that the laboratory‐derived rheologies are too strong, and thus require revision to lower strengths (Bellas et al., 2020; Zhong & Watts, 2013). Another study (Hunter & Watts, 2016), however, found that some of the same rheological laws successfully predicted the flexure of the lithosphere around the Pacific subduction zones, but required substantial weakening to adequately predict the flexure beneath Hawaiʻi.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The first is that the flexural rigidity of the lithosphere along the Hawaiian chain appears significantly weaker than predicted by the relevant, laboratory‐derived rheological laws and assuming a normal 90‐Myr geotherm (Bellas et al., 2020; Pleus et al., 2020; Zhong & Watts, 2013). Given that it is unlikely that solid‐state convection can induce such a shallow temperature anomaly, it was argued that the laboratory‐derived rheologies are too strong, and thus require revision to lower strengths (Bellas et al., 2020; Zhong & Watts, 2013). Another study (Hunter & Watts, 2016), however, found that some of the same rheological laws successfully predicted the flexure of the lithosphere around the Pacific subduction zones, but required substantial weakening to adequately predict the flexure beneath Hawaiʻi.…”
Section: Discussionmentioning
confidence: 99%
“…Conductive heat transport from the hot mantle plume (Wolfe et al., 2009), alone, is too slow, so some form of advective heat transport is needed. Three‐dimensional geodynamic models of a mantle plume interacting with the lithosphere predict that sublithospheric convection in the solid‐state can advectively erode the base of the lithosphere, but heating at depths of <50 km requires several millions of years longer (Bellas et al., 2020) than allowed by the history of rejuvenated volcanism on Oʻahu.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our description is based on purely material properties and thus does not consider any loading conditions to determine lithospheric thickness (e.g., buoyancy or plate flexure induced by the load). For the real Earth, we do not expect that T e is equivalent to z LAB as additional weakening mechanisms are not included here (such as brittle deformation, dislocation creep and low temperature plasticity; e.g., Burov & Diament, 1995; Bellas et al, 2020). In the following, we have chosen to use the classical and most familiar description to demonstrate the disctinction between our approaches in the simplest manner.…”
Section: Discussionmentioning
confidence: 99%
“…In the following, we present the viscoelastic loading model which computes the surface flexure and internal deformation of the lithosphere in response to time‐dependent loading from volcanic island building. The model has been developed and used in previous studies (Bellas et al., 2020; Zhong et al., 2003; Zhong & Watts, 2013), but we describe all essential aspects in the following and in the supporting information.…”
Section: Viscoelastic Loading Modelmentioning
confidence: 99%